Percutaneous penetration enhancement in transdermal drug delivery - Singh, Inderjeet; Sri, Prasanthi (Asian Journal of Pharmaceutics (AJP), 2014)
The transdermal route has numerous advantages over the more traditional drug delivery routes. These include high bioavailability, absence of first pass hepatic metabolism, steady drug plasma concentrations, and the fact that therapy is non-invasive. The main obstacle to permeating drug molecules is the outermost layer of the skin, the stratum corneum. Consequently, research into enhancing transdermal drug delivery (TDD) by overcoming this layer, is an area of prime interest. This review article is written to provide a coverage commentary of the recent advancements in TDD enhancement techniques.